Persepsi Perawat Pelaksana Tentang Budaya Organisasi - Mila Triana Sari (Universitas Batanghari Jambi, 2019)
Every organization has a culture that is an important factor to determine the success of the organization in achieving its objectives. Organizational culture is a shared value that is owned and reflected in the behavior of members of the organization. Organizational culture has a strong influence throughout the hospital, besides being an identity, it is also a reference or guideline for nurse behavior. This study aims to determine the nurse practitioners perception on organizational culture in the Inpatient Installation of the Mental Hospital of the Jambi Province. This research began from March to September 2018. The research method is descriptive analytics. The population of this study was 106 Nurses, with a sample involving 86 nurses. Data collection the instrument used was the modified instrument of organizational culture by Denison. The results of the study, a total of 77.9% of nurses perceiving the organizational culture good. Suggestions for hospital management are the need to socialize organizational culture for each element, need to maintain with evaluating each its component.